Integrating school and workplace learning in Canada : principles and practices of alternation education and training - Schütze, Hans Georg; Sweet, Robert Arthur, 1943- (McGill-Queen's University Press, 2003)
Contributors include Lesley Andres (University of British Columbia), Paul Anisef (York University), Paul Axelrod (York University), Laurier Caron (Université de Montréal), Nancy Émond (Université de Laval), Paul Gallagher (Gallagher and Associates), Garnet Grosjean (University of British Columbia), Marcelle Hardy (Université de Québec à Montréal), Walter Heinz (Bremen University), Ann Kitching (Gallagher and Associates), Zeng Lin (Illinois State University), Carmen Parent (Université de Québec a Montréal), Christian Payeur (Université de Laval), Tom Puk (Lakehead University), Hans G. Schuetze, Andrew Sharpe (Centre for the Study of Living Standards), Harry Smaller (York University), and Robert Sweet.